Analysis Of The Effect Of Alternator Modification On Himoinsa Genset 20 Kva To Load Testing And Cost : Analisa Pengaruh Modifikasi Alternator Pada Genset Himoinsa 20 kVA Terhadap Load Testing dan Cost - Iwan Hadi Suratno; A’rasy Fahruddin (Academia Open, 2020)
A generator is a device or engine that generates electrical energy from the presence of mechanical energy obtained from a prime mover in the form of a diesel engine as the prime mover which then drives an AC generator or alternator, causing an electrical voltage. The aim of this research is that the generator can supply electricity needs at the Sumur Welut site by changing or modifying diameter of the wire on the alternator. This analysis includes the Stator and Rotor on the Alternator generator so that it can produce the electricity needed. From the test results, the load generated after being modified can supply power at the site but the fuel consumption is more wasteful, namely 0.9 liters / minute and also the generator temperature increases to 88.2 C. So that the radiator planning is done by changing the surface area of ​​the radiator from 2915 cm2 to 8077 cm2. Or change the radiator fan, which originally changed the wind speed of 4.7 m / s to 13 m / s. Keywords: Generator, Alternator, Load Testing, Radiator, Cost.